2005
DOI: 10.1029/2005gl024743
|View full text |Cite
|
Sign up to set email alerts
|

Onset conditions for equatorial spread F determined during EQUIS II

Abstract: An investigation into the dynamics and layer structure of the postsunset ionosphere prior to the onset of equatorial spread F (ESF) took place during the NASA EQUIS II campaign on Kwajalein Atoll on August 7 and 15, 2004. On both nights, an instrumented rocket measured plasma number density and vector electric fields to an apogee of about 450 km. Two chemical release rockets were launched both nights to measure lower thermospheric wind profiles. The Altair UHF/VHF radar was used to monitor coherent and incoher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 11 publications
9
77
0
Order By: Relevance
“…See for instance Fig. 14 from Hysell et al (2005b). The existence of a seed before Spread F break up is then an experimental fact as shown by this measurement and those of Singh et al (1997), mentioned before.…”
Section: Satellites Rockets and Other Radars And Radar Techniquessupporting
confidence: 78%
See 3 more Smart Citations
“…See for instance Fig. 14 from Hysell et al (2005b). The existence of a seed before Spread F break up is then an experimental fact as shown by this measurement and those of Singh et al (1997), mentioned before.…”
Section: Satellites Rockets and Other Radars And Radar Techniquessupporting
confidence: 78%
“…An additional advantage compared with Jicamarca RTI maps is its capability to cover, almost simultaneously, a two-dimensional crosscut of close to 1000 km in the EW direction at the bottom of the F-region and all altitudes of interest (e.g. Tsunoda, 1980;Hysell et al, 2005bHysell et al, , 2006a. One of their first contributions was to show that the enhanced back scatter was related to plasma bubbles, either using only radar data (Tsunoda, 1980) or with simultaneous plasma density satellite in situ measurements (Tsunoda et al, 1982) as shown in Fig.…”
Section: Satellites Rockets and Other Radars And Radar Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…The multi-instrument programs of "Guara" campaign in Brasil (Pfaff et al, 1997) completed the spectral analysis and dynamics. The Jicamarca Julia-campaign results (Hysell and Burcham, 1998) and the Central Pacific Altair results prepared the XXIst Century experiments in the Western Pacific (Fukao et al, 2006;Hysell et al, 2005).…”
Section: Introductionmentioning
confidence: 99%